Dynamics of proteins, carbohydrates and global DNA methylation patterns during induction of nodular cluster cultures from seeds of Vriesea reitzii - Corredor, Jenny; De Conti, Daniela; Guerra, Miguel Pedro; Dal Vesco, Lirio Luiz; Pescador, Rosete (Acta Scientiarum. Agronomy, 2020)
Tissue culture techniques have been employed for bromeliad mass propagation by means of the morphogenetic route of nodular cluster cultures (NCs). This study aimed to assess protein, carbohydrate and global DNA methylation (GDM) level dynamics during NCs induction from Vriesea reitzii seeds. Seeds were inoculated into Murashige and Skoog (MS) liquid medium supplemented with 4 µM α-naphthaleneacetic acid (NAA) to induce NCs and in culture medium without plant growth regulators to form normal seedlings. Samples collected at 0, 3, 7, 10, 14, and 21 days of culture were analyzed. All parameters assessed showed the same variation pattern. However, seeds inducing NCs showed significantly lower starch (6.0 mg g-1 FM), carbohydrate (10.7 mg g-1 FM) and GDM (11.0%) levels than seeds forming normal seedlings after 21 days in culture. On the other hand, the protein content (9.1 mg g-1 FM) was significantly higher during induction. NCs induction process through seeds is the result of gene reprogramming in the explant, which leads to morphological, biochemical and metabolic alterations. This involves dedifferentiation, high cell proliferation, high energy demand and protein synthesis, which is related to elevated metabolic activity.